2000
DOI: 10.1161/01.cir.101.22.2607
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Maze Operation on Health-Related Quality of Life in Patients With Atrial Fibrillation

Abstract: Background-Maze surgery for atrial fibrillation (AF) is a curative therapy, but its effect on health-related quality of life has not been studied. Methods and Results-Maze operations were performed in 48 patients with drug-refractory AF. The majority of patients (80%) had lone AF, and the primary indication for surgery in all patients was AF. The SF-36 Health Survey was used to assess quality of life before operation and at 6 months and 1 year after surgery. Twenty-five patients were available for the 1-year f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(76 citation statements)
references
References 22 publications
4
67
0
5
Order By: Relevance
“…Several recent studies have reported the QOL of patients with AF, 14,18,19 but the present results may be difficult to compare with those studies, which used other therapies for drug-resistant AF, such as implantable cardioverter defibrillators, 19 because of the use of different QOL instruments and the lack of a comparison with the general population. One study reported the effect of the Maze operation on the QOL in patients with drug-refractory AF, 18 the majority of whom (80%) had lone AF and 63% had paroxysmal AF.…”
Section: Previous Studiesmentioning
confidence: 71%
See 1 more Smart Citation
“…Several recent studies have reported the QOL of patients with AF, 14,18,19 but the present results may be difficult to compare with those studies, which used other therapies for drug-resistant AF, such as implantable cardioverter defibrillators, 19 because of the use of different QOL instruments and the lack of a comparison with the general population. One study reported the effect of the Maze operation on the QOL in patients with drug-refractory AF, 18 the majority of whom (80%) had lone AF and 63% had paroxysmal AF.…”
Section: Previous Studiesmentioning
confidence: 71%
“…One study reported the effect of the Maze operation on the QOL in patients with drug-refractory AF, 18 the majority of whom (80%) had lone AF and 63% had paroxysmal AF. In that study of Swedish patients, the QOL of the patients with AF was significantly lower than that of the general Swedish population, but it significantly improved at 6 months after the Maze operation, and the QOL measurements obtained at both 6 months and 1 year after operation reached the levels of the general population.…”
Section: Previous Studiesmentioning
confidence: 99%
“…AF patients report greater QoL impairments relative to patients with congestive heart failure or myocardial infarction (MI) [5,9]. QoL impairments persist even in the absence of structural heart disease [7,10], and it has been found to be unrelated or only weakly correlated with indices of disease burden, frequency of episodes, illness duration, functional class, and ventricular function [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…4) Factors related to the development of permanent AF have been reported. 2,[5][6][7] A number of recent studies 3,[8][9][10][11] have associated AF and its treatment with quality-of-life issues.…”
Section: Discussionmentioning
confidence: 99%